DAMPAK LINGKUNGAN SEKOLAH TERHADAP PRESTASI BELAJAR SISWA MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Risa Sabrina; Henri Peranginangin Tanjung; Dede Indra Setiabudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of the school environment on the learning achievement of fourth-grade students at Madrasah Ibtidaiyah Ma’had Al-Zaytun. The school environment studied includes physical aspects such as school facilities, classroom comfort, and cleanliness, as well as social aspects including teacher-student interaction and peer relationships. This research used a qualitative descriptive approach. Data collection techniques included observation, interviews, documentation, and focus group discussions. Data were analyzed using data reduction, data display, and conclusion drawing. The findings show that the school environment significantly impacts students’ motivation and learning achievement. A clean and well-maintained physical environment combined with supportive social interaction provides a conducive atmosphere that improves academic results, while less supportive environments hinder learning. The study recommends schools to maintain facilities and foster a positive academic climate to optimize students’ potential. Keywords: school environment, learning achievement, qualitative study, learning achievement